2014
DOI: 10.1371/journal.pone.0097801
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Four Prymnesiophyte Algae

Abstract: Genomic studies of bacteria, archaea and viruses have provided insights into the microbial world by unveiling potential functional capabilities and molecular pathways. However, the rate of discovery has been slower among microbial eukaryotes, whose genomes are larger and more complex. Transcriptomic approaches provide a cost-effective alternative for examining genetic potential and physiological responses of microbial eukaryotes to environmental stimuli. In this study, we generated and compared the transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 82 publications
9
43
0
Order By: Relevance
“…They were affiliated with metabolic pathways including translation and ribosomal biogenesis, transcription and protein processing as well as with pathways affiliated with "Carbohydrate metabolism", "Lipid metabolism", "Nucleotide metabolism", "Amino acid metabolism" and "Signal transduction". This corresponds well with transcriptomic studies of other taxa which revealed a similar number and affiliation of genes of the core transcriptome with metabolic pathways (prymnesiophytes 1,433 core genes: Koid et al 2014; diatoms 1,370 core genes: Di Dato et al 2015). This proves the general importance of these pathways for taxa affiliated with various groups of Eukaryota.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…They were affiliated with metabolic pathways including translation and ribosomal biogenesis, transcription and protein processing as well as with pathways affiliated with "Carbohydrate metabolism", "Lipid metabolism", "Nucleotide metabolism", "Amino acid metabolism" and "Signal transduction". This corresponds well with transcriptomic studies of other taxa which revealed a similar number and affiliation of genes of the core transcriptome with metabolic pathways (prymnesiophytes 1,433 core genes: Koid et al 2014; diatoms 1,370 core genes: Di Dato et al 2015). This proves the general importance of these pathways for taxa affiliated with various groups of Eukaryota.…”
Section: Discussionsupporting
confidence: 88%
“…In our study we also tested such a sequence based method but in contrast to the results of Liu et al (2016) and Koid et al (2014) we could not identify a higher number of core genes. Genome based studies of related lineages also range from 1,666 to 3,063 core genes (Bowler et al 2008, Radakovits et al 2012.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations